Theories of Change for Complex Sustainability Transformations: Mobilizing the Potential of Redefining the Relationship Between Humans and Nature - Tilman Hertz (Journal of MultiDisciplinary Evaluation)
Central to transformations towards sustainability is the call to redefine the relationship between humans and nature. This redefinition represents a paradigm shift, with many asserting that it holds the greatest potential for transformation. However, the practical implementation of this call often remains abstract for those responsible for interventions in sustainability, such as projects and programs. This paper aims to initiate the translation of this call into actionable steps for the design of Theories of Change. It will achieve this by bringing three approaches into dialogue: Principles-focused, Complexity-aware, and Decolonization approaches.